Inverted Flap Technique for Posttraumatic macula Hole Surgery in a Young Male Patient in Sub-Saharan Africa - Oderinlo, Olufemi; Hassan, Adekunle Olubola; Okonkwo, Ogugua (Medical Science: Trends and Innovations Vol. 4, 2025)
Posttraumatic macular holes (MHs) are uncommon but often challenging to manage, especially in resource-limited settings such as sub-Saharan Africa. We present the case of a young male patient who underwent successful post-traumatic MH repair using the inverted internal limiting membrane (ILM) flap technique, combined with air tamponade and a one-day face-down positioning protocol. This approach demonstrated excellent anatomical and visual outcomes despite the complexity associated with traumatic MHs. The case highlights the potential of this modified surgical strategy as a cost-effective and efficient alternative to standard techniques, particularly in settings with limited access to prolonged gas tamponade and advanced postoperative care. Further studies and clinical trials are warranted to validate the safety and efficacy of this technique in similar cases globally.